The complete genome resource of Xanthomonas oryzae pv. oryzae CIX2779 includes the first sequence of a plasmid for an African representative of this rice pathogen - (:unkn) unknown (My University, 2023)
The bacterial plant pathogen Xanthomonas oryzae pv. oryzae is responsible for the foliar rice bacterial blight disease. Genetically contrasted, continent-specific, sublineages of this species can cause important damages to rice production both in Asia and Africa. We report on the genome of the CIX2779 strain of this pathogen, previously named NAI1 and originating from Niger. Oxford Nanopore long reads assembly and Illumina short reads polishing produced a genome sequence composed of a 4,725,792-bp circular chromosome and a 39,798-bp-long circular plasmid designated pCIX2779_1. The chromosome structure and base-level sequence are highly related to reference strains of African X. oryzae pv. oryzae and encode identical transcription activator-like effectors for virulence. Importantly, our in silico analysis strongly indicates that pCIX2779_1 is a genuine conjugative plasmid, the first indigenous one sequenced from an African strain of the X. oryzae species.Copyright (c) 2022 The Author(s). This is an open access article distributed under the .
Keywords: African Research